(untitled) (Research, Society and Development, 2021)
Goal: Introduce the usage of the TIC podcast as a potential tool, based on prior scientific research, to boost the development of professional nutritionists. Methodology: a transversal, quantitative and descriptive study was carried out with professional nutritionists from the Brazilian territory, of both sexes. Data was collected online through a questionnaire developed in “Google Forms” and self-filled by the volunteer. Data related to sociodemographic and occupational profile, predominant type of social network consumed, health conditions and aspects related to the area of professional activity were collected. Results: Out of the 115 volunteers, 95% are women, 48.7% reported receiving more than 3 minimum wages, 46.95% receive from 1 to 3 minimum wages, in addition to data collected on issues that emphasized the labor journey, satisfaction with the profession, occupation area, challenges and motivations for changing the profession. Based on the analysis of this information, the first 10 themes were chosen for the creation of podcasts, debut and presentation, society of tiredness and productivity, professional devaluation, being a woman and its various roles/functions, weight stigma and aesthetic pressure in the profession , occupational stress and burnout syndrome, binge eating, career development, nutrition and digital influencers, and impunity. Conclusion: It is concluded that after scientific investigation, the data showed a dissatisfaction of nutritionists with the profession, desiring greater professional appreciation and that the podcast has the potential to be a credible tool, capable of meeting labor needs.